Incidence and predictors for abnormal liver function during direct-acting antiviral agents in chronic hepatitis C patients. Issue 37 (11th September 2020) - Liu, Yen-Chun; Jeng, Wen-Juei; Cheng, Ya-Ting; Hsieh, Yi-Chung; Teng, Wei; Chen, Yi-Cheng; Lin, Chun-Yen; Chien, Rong-Nan; Sheen, I-Shyan
Abstract : Abstract: Abrupt alanine aminotransferase (ALT) elevation during direct-acting antiviral agents (DAA) treatment is an uncommon but noticeable adverse event in chronic hepatitis C (CHC) patients, which may lead to early termination of treatment. This study aims to investigate the incidence, outcome and predictors of the on-treatment ALT elevation during DAA therapy. CHC patients treated with DAA regimen in Chang Gung Memorial Hospital, Linkou branch during March 2015 to March 2019 were recruited. Prospective scheduled ALT assessment at baseline, 2nd, 4th, 8th, and 12th/24th weeks were recorded. Pretherapy host and viral factors were compared between patients with and without on-treatment ALT elevation. Multivariate logistic regression was used for independent factors for on-treatment ALT elevation. A total of 1563 CHC patients treated with grazoprevir/elbasvir, glecaprevir/pibrentasvir and sofosbuvir-based regimen were analyzed. On-treatment ALT elevation occurred in 10.9% patients while those treated with glecaprevir/pibrentasvir had the least possibility (5.4%). Only 1.4% patients had ≥grade 3 ALT elevation events. The presence of such events had no impact on sustained virological response 12 rates. Hepatitis B virus coinfection (aOR: 3.599, P < 0.001) and higher pretherapy ALT (1-5x, ≥5x upper limit of normal: aOR: 2.632, P = 0.024, aOR: 4.702, P = .011, respectively) were significant predictors for ALT elevation. On-treatment ALT elevation occurred in one-tenth CHC patients treated with preferred DAAs but had no impact on sustained virological response rate. Abstract : Supplemental Digital Content is available in the text